2023
DOI: 10.1136/archdischild-2023-325300
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-high frequency lung ultrasound in preterm neonates: a test validation study on interpretation agreement and reliability

Abstract: ObjectiveTo verify if increasing frequency, through the use of ultra-high frequency transducers, has an impact on lung ultrasound pattern recognition.DesignTest validation study.SettingTertiary academic referral neonatal intensive care unit.PatientsNeonates admitted with respiratory distress signs.InterventionsLung ultrasound performed with four micro-linear probes (10, 15, 20 and 22 MHz), in random order. Anonymised images (600 dpi) were randomly included in a pictorial database: physicians with different lun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Nonetheless, previous studies have demonstrated equally optimal interobserver agreement for lung ultrasonography interpretation with or without operators’ blinding. 3 , 23 , 24 Lung ultrasonography values of 6 and 8 were the prespecified positive cutoffs, as these have been associated with the highest global accuracy in early preterm neonates 7 , 14 ; thus, we used them to investigate noninferiority in the study population. The reference standard was an FiO 2 level of 0.30, as this is the threshold suggesting surfactant administration in the European guidelines 20 and is widely used.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, previous studies have demonstrated equally optimal interobserver agreement for lung ultrasonography interpretation with or without operators’ blinding. 3 , 23 , 24 Lung ultrasonography values of 6 and 8 were the prespecified positive cutoffs, as these have been associated with the highest global accuracy in early preterm neonates 7 , 14 ; thus, we used them to investigate noninferiority in the study population. The reference standard was an FiO 2 level of 0.30, as this is the threshold suggesting surfactant administration in the European guidelines 20 and is widely used.…”
Section: Methodsmentioning
confidence: 99%
“…In detail, clinicians not performing ultrasonography were unaware of the LUS, but it was impossible to conceal patient conditions, such as vital monitoring and clinical appearance, to investigators performing ultrasonography. Nonetheless, previous studies have demonstrated equally optimal interobserver agreement for lung ultrasonography interpretation with or without operators’ blinding . Lung ultrasonography values of 6 and 8 were the prespecified positive cutoffs, as these have been associated with the highest global accuracy in early preterm neonates; thus, we used them to investigate noninferiority in the study population.…”
Section: Methodsmentioning
confidence: 99%
“…This can be interesting as these probes have higher superficial resolution and can be used for the same purpose in adults too. It remains to be established if ultra-high frequency probes can further improve the measurement [ 12 ]. It is conceivable that the inspiratory-expiratory difference could have a role in the detection of pneumothorax (where the lung sliding is abolished) or the evaluation of lung overdistention but these are interesting hypotheses to be verified in dedicated studies.…”
mentioning
confidence: 99%